PENGARUH LITERASI KEUANGAN, PENDAPATAN, DAN TOLERANSI RISIKO TERHADAP KEPUTUSAN INVESTASI EMAS - Jesi Sefina Hoky; Safitri, Teti Anggita (JURNAL ILMIAH EDUNOMIKA, 2025)
Rapid developments in the era of globalization encourage the importance of a strong understanding of finance and the ability to manage money resources. Good financial management helps individuals make better decisions, especially in investment. Gold investment is a popular choice because of its safe and liquid nature, especially amidst global economic uncertainty. Although investment in Indonesia is still relatively low, good financial literacy can increase the interest and ability of the community, especially students to invest in gold. This study aims to determine whether there is an influence of financial literacy, income, and risk tolerance on gold investment decisions. This study uses a quantitative research type with associative analysis. The sample used is active students of Universitas 'Aisyiyah Yogyakarta who have or are currently using gold investment. The data collection method in this study uses primary data through the distribution of questionnaires online to all students of Universitas 'Aisyiyah Yogyakarta. The results of this study explain that Financial Literacy (X1), Income (X2), and Risk Tolerance (X3) have a significant effect on gold investment decisions.